Analisis Kenerja Maximum Power Point Tracker (MPPT) Pada Sistem Photovoltaic Standalone Berbasis Algoritme Perturb And Observe (P&O) - Tetuko, Agim; Djuniadi, Djuniadi; Apriaskar, Esa (PROtek : Jurnal Ilmiah Teknik Elektro, 2021)
A solar power plant or photovoltaic (PV) is a generator that converts energy from light into pollution-free electrical energy. However, changes in the intensity of solar radiation and ambeint temperature Photovoltaic (PV) which are not linear are the main problems of PV systems in efficient energy conversion that occurs. Control using the Maximum Power Point Tracker (MPPT) method based on the Perturb and Observe (PO) algorithm which is applied to overcome these problems. Maximum Power Point Tracker (MPPT) itself is a technique for tracking the maximum output power point of the PV system. MPPT will change the working point so that the converter will force the work of the solar panels according to their ability to always reach the maximum power point. MPPT is not a mechanical system that makes the solar panel system move according to the direction of the sun's intensity, but an electronic system that works to optimize the power output from the solar panel. Meanwhile, Algorithm (PO) works by detecting and disturbing the PV voltage periodically by varying its duty cycle, as well as observing the PV power to be able to increase and decrease the PV voltage in the next 3 cycles. This paper presents an analysis of the MPPT PO performance with a standalone system implemented in the campus area. In this study, the applied PV system was able to produce a maximum power of 1626.087 Watts under optimal irradiation conditions and temperature. As well as testing the PV system under radiation and temperature conditions in the location study, namely FT UNNES. The maximum power of the PV system is 227.585 Watt.